2017
DOI: 10.1002/pds.4376
|View full text |Cite
|
Sign up to set email alerts
|

Decline in opioid prescribing after federal rescheduling of hydrocodone products

Abstract: The 2014 federal policy was associated with a decrease in rates of HCP and total opioid prescribing. The large decrease in the rates of HCP prescribing for patients with actively treated cancer may represent an unintended consequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 40 publications
6
49
1
Order By: Relevance
“…Using pharmacy data, one study reported a 22% fewer dispensed hydrocodone combination product prescriptions in the 12 months after than the 12 months before rescheduling. We have previously reported a 26% relative decrease in hydrocodone prescriptions from a monthly rate of 2.7% in 2013 to 2.0% in 2015 in a commercially insured population aged 18 to 64 . This compares with a 18.7% relative decrease in monthly rate of hydrocodone prescription from 7.2% in 2013 to 5.8% in 2015 that we found in the older Medicare population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Using pharmacy data, one study reported a 22% fewer dispensed hydrocodone combination product prescriptions in the 12 months after than the 12 months before rescheduling. We have previously reported a 26% relative decrease in hydrocodone prescriptions from a monthly rate of 2.7% in 2013 to 2.0% in 2015 in a commercially insured population aged 18 to 64 . This compares with a 18.7% relative decrease in monthly rate of hydrocodone prescription from 7.2% in 2013 to 5.8% in 2015 that we found in the older Medicare population.…”
Section: Discussionsupporting
confidence: 89%
“…Although some single centers reported an increase in tramadol prescribing after the rescheduling, our findings of no change in tramadol prescribing are similar to our previous nationwide study in a younger, commercially insured population …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous studies that have that shown limited substitution effects among closed cohorts of HCP users that were analyzed before and after the schedule change . Studies that have reported increases in the use of alternative analgesics after HCP rescheduling have been primarily set in emergency departments, poison control centers and single provider outpatient settings, and their findings are likely to represent the impact of system‐level changes on both new and continuing HCPs users .…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have examined in the impact of the hydrocodone schedule change on opioid prescribing. These studies have consistently demonstrated that the upscheduling decreased the prescribing and dispensing of both hydrocodone combination products and opioids in general . For example, an analysis of nationwide prescription sales data indicated that the schedule change was associated with 1.1 billion fewer hydrocodone combination product tablets and 26.3 million fewer prescriptions during the year after it went into effect .…”
Section: Introductionmentioning
confidence: 99%